2013
DOI: 10.1016/j.acha.2012.07.006
|View full text |Cite
|
Sign up to set email alerts
|

On the polarizability and capacitance of the cube

Abstract: An efficient integral equation based solver is constructed for the electrostatic problem on domains with cuboidal inclusions. It can be used to compute the polarizability of a dielectric cube in a dielectric background medium at virtually every permittivity ratio for which it exists. For example, polarizabilities accurate to between five and ten digits are obtained (as complex limits) for negative permittivity ratios in minutes on a standard workstation. In passing, the capacitance of the unit cube is determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
86
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(87 citation statements)
references
References 49 publications
(141 reference statements)
1
86
0
Order By: Relevance
“…In fact, P s (P e − P i )P s is intimately connected to Poincaré's variational problem of inner and outer energies. To explain our point of view, let us briefly recall and combine some of the ideas of [9] and [11]. The analogies with the previous work of this section should be clear.…”
Section: Theorem 34mentioning
confidence: 99%
See 3 more Smart Citations
“…In fact, P s (P e − P i )P s is intimately connected to Poincaré's variational problem of inner and outer energies. To explain our point of view, let us briefly recall and combine some of the ideas of [9] and [11]. The analogies with the previous work of this section should be clear.…”
Section: Theorem 34mentioning
confidence: 99%
“…The arguments essentially follow those of [11], with some additional technicalities, addressed in [9], arising from the fact that K is no longer a compact operator on the scale H s of Besov spaces, 0 ≤ s ≤ 1.…”
Section: The Angle Operatorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fuchs [1975] showed that there are six major static resonances between r = −0.42, and r = −3.68. However, as pointed out by Helsing and Perfekt [2013], some of them may be artifacts due to insufficient resolution or unintended rounding of the corners. Be that as it may, there are no such things as infinitely sharp corners or wedges described by the bulk permittivity in the physical world.…”
Section: Numerical Resultsmentioning
confidence: 99%